2009
DOI: 10.1080/00085030.2009.10757598
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Evaluations by Drug Recognition Experts in Canada

Abstract: The objective of this paper is to illustrate the accuracy with which police officers trained as Drug Recognition Experts (DREs) can identify the category of drug(s) ingested by persons suspected of being impaired as the result of drug use. The study examined 1,349 drug evaluations completed by DREs in Canada to determine the extent to which DRE opinions about the category of drug(s) used matched the results of toxicological analysis of fluid samples. The paper presents measures of sensitivity, specificity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
1
4
0
Order By: Relevance
“…Nevertheless, focusing initial attention on the key signs and symptoms identified in this research may enhance the validity, effectiveness, and efficiency of drug detection and identification by DREs and may lead to a more effective and efficient DEC program, improved enforcement of drug-impaired driving, and greater acceptance of the DEC program by the courts. The findings from the present study add to the accumulating evidence of the validity and accuracy of the DEC program (Beirness et al 2007(Beirness et al , 2009Smith et al 2002) and will help to further support the program and the work of its DREs.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, focusing initial attention on the key signs and symptoms identified in this research may enhance the validity, effectiveness, and efficiency of drug detection and identification by DREs and may lead to a more effective and efficient DEC program, improved enforcement of drug-impaired driving, and greater acceptance of the DEC program by the courts. The findings from the present study add to the accumulating evidence of the validity and accuracy of the DEC program (Beirness et al 2007(Beirness et al , 2009Smith et al 2002) and will help to further support the program and the work of its DREs.…”
Section: Discussionsupporting
confidence: 58%
“…A review of existing laboratory and field evaluation studies on the DEC program reported the overall accuracy of DEC evaluations made by trained DREs on impaired drivers to be more than 80% (Beirness et al 2007). A study of 1,349 DEC evaluations completed by DREs in Canada reported an overall accuracy rate of 95% (Beirness et al 2009), with some drug classes being more difficult to detect than others. Taken together, these research findings (Beirness et al 2007(Beirness et al , 2009 provide confidence in the use of the DEC procedure to detect persons impaired by substances other than alcohol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• An officer trained in drug identification has a 95% accuracy rate in identifying the type of drug causing impairment [21].…”
Section: Detection Of Cannabis Use By Impaired Driversmentioning
confidence: 99%
“…Psychophysical and visual examinations have been previously shown to produce reliable indicators of cannabis intoxication in impaired driving cases (Hartman et al, 2016), but less is known about the effectiveness of standard impairment testing in the specific population of medical cannabis users. drug impairment in Canada (Beirness et al, 2009;Porath-Waller & Beirness, 2010;Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%